Edukasi Lingkungan Anak Sekolah Dasar melalui Petualangan Jelajah Alam di Desa Cingebul - Fernando, Frendi; Azizah, Nadya Rizky; Hidayat, Mohamad Syarif; Urohmah, Annisa; Mu'ajizin, Mohamad Kholis; Nabila, Annisa Alivia; Rahsanindya, Hartika Esti; Baedah, Jaeny Nur; Lia, Ceci; Amelia, Ria; Salsabila, Alfi; Hilda, Nurul (Jurnal Pengabdian Masyarakat Bangsa, 2025)
Environmental education for elementary school children is a crucial intervention for sustainable development. This community service program aims to improve understanding of ecosystems, strengthen awareness of maintaining cleanliness, and foster environmental awareness among elementary school students in Cingebul Village, considering that they are at the concrete operational cognitive development stage that enables conceptual understanding through direct experience. The method used is an experiential learning approach through the "Nature Exploration Adventure" program, which is designed interactively, reflectively, and creatively. Main activities include ecosystem exploration, observation of environmental components, and educational games on waste management. The program evaluation results showed a significant increase in understanding of ecological concepts among participants, demonstrated by enthusiasm and a more proactive attitude towards maintaining environmental cleanliness. This experiential learning approach has proven effective as an environmental education strategy for elementary school children, therefore it is highly recommended for wider implementation to shape a generation that is aware of and responsible for environmental sustainability.